Mononuclear and Binuclear Complexes of Fe(II) and Cu(II) with 2,6-Diacetyl Pyridine and Phenlene Monoxime and Phenylene Diamine - Kumar, R.N.; Chauhan, N.K.; Kumar Singh, Sudhir (Asian Journal of Chemistry, 2010)
Mononuclear and binuclear complexes of types (ML1-H2], [ML1]X2, [ML2]2X4, [ML3]2X4, [M(L2-H2)]2, [ML3-H2]2 where M = Fe(II) or Cu(II), X = OAc– or 0.5SO2–4, L1 = bis-(2,6-diacetyl pyridine monoxime) 1,2-diamino benzene, L2 = bis-(2,6-diacetylpyridine monoxime) 1,3-diamino benzene, L3 = bis-(2,6-diacetyl pyridine monoxime) 1,4-diaminobelizene have been synthesised and characterised by elemental analysis, IR electronic and magnetic susceptibility studies.